The Effect of Brandt Daroff Exercise on the Balance of Vertigo Patients in the Cut Meutia Room of TK II Iskandar Muda Hospital Banda Aceh - Sunita, Sunita; Mulfianda, Riyan; Desreza, Nanda (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Vertigo is a disorder of balance against gravity with symptoms of dizziness, spinning like floating, the world seems to turn upside down. Vertigo can be brief or prolonged, lasting for hours or days. Complaints of vertigo come suddenly and are felt continuously until the patient cannot sleep. The Brandt-Daroff exercise is a treatment for vertigo that helps speed up recovery, prevent future episodes, and improve balance without needing medication. This vertigo exercise increases blood flow to the brain, allowing the body's balancing mechanism to operate better and the sensory system to do its job more efficiently. The goal of this study was to see how brandt daroff exercise affected the balance of vertigo patients at the Cut Meutia Room at Tk II Iskandar Muda Hospital in Banda Aceh. This type of research is a quasy experiment method with a one group pretest and postest design approach, this research was conducted in January-July 2024. The population and sample were all vertigo patients totaling 43 people and the sampling method used total sampling technique. Data collection using observation sheets and questionnaires. This study's data analysis methods include univariate and bivariate analysis, as well as statistical testing with the Wilcoxon signed rank test. The results of the study; there is an effect of brandt daroff exercise on the balance of vertigo patients with p-value = 0.007. Hence, Tk II Iskandar Muda Hospital is expected to train nurses on the importance of brandt daroff exercises to help reduce vertigo symptoms in patients.